Twenty First Century Global Goal-Setting Addressing Global Inequality: An Interdisciplinary Ethical Analysis - O'Sullivan, James P. (Religions, 2017)
This paper employs an interdisciplinary ethical analysis to evaluate how global inequality has been addressed by recent so-called global goal-setting initiatives. It seeks to contextualize these initiatives within theoretical paradigms of human rights and human development, and to utilize these paradigms in evaluating the successes and shortcomings of the goal-setting initiatives. It concludes that while these initiatives have achieved some success in addressing global inequality, much still remains to be done.